Serviceability limit states of high performance reinforced concrete beams with hybrid fibre - Piotr Smarzewski (Budownictwo i Architektura, 2013)
The article presents the results of research and analysis of reinforced high performance concrete beams with steel and polypropylene fibres at service load. The beams were bent in the 4-point model. Research was carried out for three different rectangular reinforced concrete beams in terms of the quantity and the type of reinforcement. The beam B1 was constructed conventionally with reinforced steel rods. The beams B2 and B3, instead of the compressive rods and the stirrups the fibre reinforcement of variable fibre volume percentage was applied. In the tests a non-contact system for three-dimensional measurements of deformation – ARAMIS was used. The analysis of the behaviour of the beams under static load for serviceability was based on: images of cracks, strain and force – displacement curves.